Combined vacuum-assisted closure treatment with laparoscopic mobilization of an omental flap and meshed skin grafts for reconstruction of infected sternotomy wounds : two cases - Veir, Zoran (Array, 2009)
Abstract: In cardiac surgery, poststernotomy wounds are life threatening complications, with mortality up to 50%. We described two patients, who underwent coronary artery bypass grafting and postoperatively developed a deep sternal wound infection. Reconstruction was combined with vacuum-assisted closure treatment, laparoscopic mobilization of an omental flap and split thicknes skin grafts. The omental flap is a well-vascularized local flap with a large surface area and has excellent immunologic and angiogenic properties. Both patients recovered completely. In our opinion, vacuum-assisted closure treatment and laparoscopic mobilization of great omentum is suitable option for treating deep sternal wounds